2022
DOI: 10.3389/fbioe.2022.816652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Concentrations of Silver Nanoparticles on the Quality of the Chemical Bond of Glass Ionomer Cement Dentine in Primary Teeth

Abstract: Background: The nanotechnologies have been applied for dental restorative materials manufacturing such as glass ionomer cement, composites, tooth regeneration, and endodontic sealers. The study aimed to investigate the chemical bond of conventional glass ionomer cement and to evaluate the addition of different concentrations of silver nanoparticles (AgNPs) on the quality of the chemical bond of glass ionomer cement to primary dentin.Methods: Silver nanoparticle (AgNP) powder was added in concentrations of 0.2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The fluoride release characteristics of glass ionomer have been investigated in several studies [24,[28][29][30]. These studies clearly showed that the fluoride release characteristics of glass ionomers were inversely proportional to the number of fillers added regardless of their type [24,31]. These findings are in agreement with the results observed in the present study and the authors found that the higher the concentration of silver nanoparticles was, the lower the amount of fluoride released was.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The fluoride release characteristics of glass ionomer have been investigated in several studies [24,[28][29][30]. These studies clearly showed that the fluoride release characteristics of glass ionomers were inversely proportional to the number of fillers added regardless of their type [24,31]. These findings are in agreement with the results observed in the present study and the authors found that the higher the concentration of silver nanoparticles was, the lower the amount of fluoride released was.…”
Section: Discussionsupporting
confidence: 90%
“…However, the relationship between the amount of fluoride inside each cement and the ability of this cement to release the fluoride inside is still not well understood. It was found that three main mechanisms can explain fluoride release from glass ionomers, including the diffusion of ions through pores by superficial rinsing; microfractures on the surface, which enable fluoride ion leaching; and, finally, the mass diffusion concept [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…More than that, the long-term efficiency of the CuNP/antibiotic composite seems superior to that of the AgNP/antibiotic composite, suggesting a prolonged effect; in our opinion, this is due to the phytoconstituents acting as capping agents for the NPs. The concentration of NPs in the final composite must be carefully selected, as a higher concentration could alter the bond quality with dentin interaction, as demonstrated by Abed et al [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“… NPs, Ref. NPs Characteristics GIC Experimental Study Findings CuNP [ 44 ] Phytosynthesized using Thymus vulgaris extract, spherical, 10-25 nm GC Fuji IX GP ® (type II ii ) 0.5% NPs, respectively 0.5% NPs + 1.5% metronidazole in GIC, antimicrobial effect tested against Staphylococcus aureus and Streptococcus mutans ; compressive strength measurements Addition of CuNPs enhanced antimicrobial properties, while not affecting the mechanical properties: IZ = 20/29 mm ( S. aureus), 19/26 mm ( S. mutans ) after 1 day, 15/19 mm ( S. aureus), 13/18 mm ( S. mutans ) after 1 month; CS = 44.2/43.9 MPa AgNP [ 44 ] Commercially available, 20–50 nm Addition of AgNPs led to superior antimicrobial properties compared with other variants (including CuNPs), while not affecting the mechanical properties: IZ = 24/30 mm ( S. aureus), 20/27 mm ( S. mutans ) after 1 day, 16/18 mm ( S. aureus), 14/17 mm ( S. mutans ) after 1 month; CS = 45.9/45.0 MPa AgNP [ 45 ] Commercially available, under 100 nm GC Fuji II GP ® (type II ii ) 0.2, 0.4, respectively 0.6%NPs in GIC, evaluation of the quality of the chemical bond of GIC to primary dentin by FTIR Concentrations above 0.4% AgNP in GIC altered the bond quality with dentin interaction; addition of AgNPs at low level improves the mechanical properties while maintaining the bond quality AgNP [ 46 ] Phytosynthesized using Cupressus macrocarpa extract, spherical, 13.5–25.8 nm GC Fuji IX GP ® (type II ii ) 0.5%NPs, respectively 0.5%NPs + amoxicillin in GIC, antimicrobial effect tested against Staphylococcus aureus and Streptococcus mutans ; co...…”
Section: Resultsmentioning
confidence: 99%
“…The results of the study must be observed along with some limitations, as it is an in vitro study. In vitro studies are useful to explain some conditions of materials separate from when they are exposed in the oral cavity [42,43]. Therefore, the results cannot be extrapolated to clinical practice, since multiple factors are acting simultaneously on the dental materials.…”
Section: Discussionmentioning
confidence: 99%